Organisational Climate and Pro-environmental Behaviours at Work: The Mediating Role of Personal Norms - Mouro, Carla; Duarte, Ana Patrícia (Frontiers in Psychology, 2021)
Organisations are currently strongly encouraged to adopt more responsible production patterns aligned with sustainable development goals. Pro-environmental behaviours (PEBs) in the workplace can strengthen the expected positive impacts of organisations’ environmental performance and engender more sustainable transitions to low-carbon production. Research on PEBs at work is relatively recent, so this field still lacks studies of the role of organisational policies and practices in workers’ adoption of these behaviours and of psychosocial processes that contribute to more sustainable workplaces. The present research examined how perceptions of organisations’ environmental policies and practices (i.e. organisational climate or injunctive norms) and of coworkers’ PEBs (i.e. descriptive norms) affect employees’ self-reported voluntary PEBs. Thogersen’s norm taxonomy model was also applied to address the role of personal norms. Self-commitment to sustainable goals at work can play a fundamental role in workers’ behavioural choices, so this research further investigated whether personal norms mediate the relationship between perceived pro-environmental organisational climate and reported workplace PEBs. To test the proposed model, data were collected on 210 workers from different business sectors, who completed an online questionnaire. The analyses showed that, after controlling for the effects of tenure, education level and a management position, a pro-environmental organisational climate predicts stronger personal norms and a greater tendency to adopt PEBs at work (adjusted R squared = 0.36), providing evidence of complete mediation. Coworkers’ perceived descriptive norms also contribute directly to self-reported PEBs. The discussion of the results focuses on the importance of organisational level initiatives as a way to promote change in individuals’ behaviours, which can have positive consequences for workplaces’ transition to sustainability.